2020
DOI: 10.1093/hmg/ddaa236
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association and characterization ofFSTL5in isolated clubfoot

Abstract: Talipes equinovarus (clubfoot, TEV) is a congenital rotational foot deformity occurring in 1 per 1000 births with increased prevalence in males compared to females. The genetic etiology of isolated clubfoot (iTEV) remains unclear. Using a genome-wide association study, we identified a locus within FSTL5, encoding follistatin-like 5, significantly associated with iTEV. FSTL5 is an uncharacterized gene whose potential role in embryonic and post-natal development were previously unstudied. Utilizing multiple mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Results from a recent study associate variation of FSTL5 expression in prehypertrophic chondrocytes with lower limb malformations and congenital rotational foot deformity [99].…”
Section: Pathologies Of Osteo-and Myohistogenesismentioning
confidence: 99%
“…Results from a recent study associate variation of FSTL5 expression in prehypertrophic chondrocytes with lower limb malformations and congenital rotational foot deformity [99].…”
Section: Pathologies Of Osteo-and Myohistogenesismentioning
confidence: 99%
“…43 Most commonly, it is an isolated disorder considered to have a complex and poorly understood genetic component that is likely impacted by a spectrum of genetic loci. 44 The prenatal development of congenital clubfoot remains poorly understood. On clinical exam, plantar flexion is observed at the ankle, hindfoot varus, forefoot adduction, and inversion.…”
Section: Foot Deformitiesmentioning
confidence: 99%
“…Yet, the association between isolated CTEV and SNPs in proximity to NCOR2 / ZNF664 , FOXN3 , MMP7 / TMEM123 or SORCS1 genes was determined in discovery and replication datasets 78. Another GWAS indicated rs76973778 SNP located in the intron of FSTL5 gene as the associated variant both in the discovery and replication cohorts but animal studies showed no developmental abnormalities in rats heterozygous or homozygous for Fstl5 79…”
Section: The Genetic Etiology Of Isolated Clubfootmentioning
confidence: 99%